"Is It a Classic if No One Reads It?" Relevance Theory and the Canon - Furlong, Anne (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
Most of the current debates about the canon stem from negative attitudes that have to do with the shaping of the canon; the notion of the canon; and whether it is possible to read any text except through the prism of ideology. However, the nature of canons and canonical works in non-literary disciplines such as linguistics or sociology has been largely overlooked, as have the cognitive principles that influence the selection of canonical works in any discipline. Relevance theory permits a description of non-spontaneous interpretation which permits us to argue that a given text is or is not a literacy work. However, the inclusion of a work in the canon of any discipline is not necessarily a function of its being “literary”, but rather of the degree to which it forms a highly salient or necessaiy part of the context in which current works are intended to be interpreted. I conclude that literary classics, at least, must be read in order to qualify as canonical.